Algebraic curves over a finite field - Hirschfeld, J. W. P. (James William Peter), 1940-; Korchmáros, G.; Torres, F. (Fernando) (Princeton series in applied mathematics., 2008)
This book provides an accessible and self-contained introduction to the theory of algebraic curves over a finite field, a subject that has been of fundamental importance to mathematics for many years and that has essential applications in areas such as finite geometry, number theory, error-correcting codes, and cryptology. Unlike other books, this one emphasizes the algebraic geometry rather than the function field approach to algebraic curves. The authors begin by developing the general theory of curves over any field, highlighting peculiarities occurring for positive characteristi.